Sprawozdanie z seminarium naukowego „Polowanie w XXI wieku »Dobrzy myśliwi« i »złe bobry«, czyli aporie cywilizacji” Katowice, 10 stycznia 2017 roku - Sokół, Aneta M. (Zoophilologica. Polish Journal of Animal Studies, 2017)
Aneta M.Sokół's report on the seminar titled "Hunting in the 21st Century. »Good hunters« and »bad beavers«, i.e. aporias of civilisation" organized in Katowice on January10th, 2017.